Comparison between two ovulation-inducing drugs in mares - Silva, Paula Cardoso de Almeida; Oliveira, Jhonnatha Paulo; Paiva, Sávio Oliveira; Caram, Diogo Fabrício; Junqueira, Renato Guerra de Castro; Jacob, Julio Cesar Ferraz; Sá, Marcus André Ferreira (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Silva P.C.A., Oliveira J.P., Sá M.A.F., Paiva S.O., Caram D.F., Junqueira R.G.C. & Jacob J.C.F. [Comparison between two ovulation-inducing drugs in mares.] Comparação entre dois agentes indutores da ovulação em éguas. Revista Brasileira de Medicina Veterinária, 38(Supl.2):45-48, 2016. Departamento de Reprodução e Avaliação Animal, Instituto de Zootecnia, Universidade Federal Rural do Rio de Janeiro, BR-465, Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: paulinha_calmeida@hotmail.com Hormonal control of the ovulation is an effective tool to improve reproductive performance and reduce costs in equine breeding programs. The aim of this study was to compare the efficiency of lower doses of hCG and Deslorelina than doses traditionally used, evaluating the follicular parameters and time between induction and ovulation. Induction of ovulation was performed according to the groups, 1000 IU of hCG (G1), 0.75mg of Deslorelin (G2), and 1.0ml of saline solution (G3). Twenty-four hours after administration, ovaries were evaluated by ultrasound every six hours until detection of ovulation. The percentage of ovulation within 36 hours was 34.4%, 13.3% and 8.7%, and up to 42 hours was 96.9%, 70% and 17.4% for G1, G2 and G3, respectively, showing a significant increase (p ˂ 0.0001) in G1 compared to other groups. In G2 there was a significant increase (p ˂ 0.0001) of ovulation after 42 hours from the induction, and G3 after 48 hours. Until 48 hours the percentage of induction of ovulation was 96.8% (31/32) 90% (27/30) and 30.4% (7/23), respectively, for G1, G2 and G3. Thus, the lower doses of ovulation-inducing drugs were effective in inducing ovulation within 48 hours, however hCG was faster than deslorelin, which might reduce costs and help the reproduction management.